LANGUAGE USE: A STUDY OF DECLARATIVE ACTS USED BY THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 1 TEJAKULA - ., Ni Luh Bendi Arfani; ., Prof. Dr. Dewa Komang Tantra,Dip.,App.; ., Ni Komang Arie Suwastini, S.Pd,M.Hum. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk mengidentifikasi Declarative Acts dari siswa Jurusan Bahasa. Declarative Acts adalah salah satu jenis dari Speech Acts yang merubah dunia melalui ujaran dan melalui kata-kata (Yule, 2008), dengan kata lain itu merupakan cara mengekspresikan fakta-fakta. Penelitian ini merupakan penelitian kualitatif yang memiliki 4 tujuan; yaitu mendescripsikan mavcam-macam Declarative Acts yang digunakan oleh siswa, mengidentifikasi gaya bahasa dari Declarative Acts siswa Jurusan Bahasa, mengidentifikasi kesalahan yang dilakukan oleh siswa dalam hal grammar dan diction, dan mengidentifikasi sebab dari kesalahan-kesalahan yang dilakukan oleh siswa dala Declarative Acts mereka. Penelitian ini menggunakan metode pancingan dan perekam, pedoman wawancara, dan catatan sebagai alat dalam mengumpulkan data. Kumpulan data kemudian ditulis kembali, dianalisis dan dikategorikan, dan kemudian hasilnya dideskripsikan. Hasil dari penelitian ini menunjukkan bahwa siswa Jurusan Bahasa lebih sering menggunakan lima kategori Declarative Acts yang lebih dominan adalah to approve, then followed by to disapprove, to name, to call, and the last is to bless. Mereka juga tidak jauh dalam melakukan kesalahan. Mereka lebih sering melakukan kesalahan pada grammar dan diikuti oleh diction. Dari kesalahan-kesalahan siswa, ada lima penyebab kesalahan dalam Declarative Acts siswa; yaitu interlingual errors, ignorance of rule restrictions, incomplete application of rules, false concept hypothesized, and developmental errorsKata Kunci : Speech Acts, Declarative Acts, siswa Jurusan Bahasa This study aimed to identify the Declarative Acts of Language Program students. Declarative Acts are those kinds of speech acts that change the world via their utterance and via words (Yule,2008), in other word it is way in expressing facts. This study is a qualitative study that has 4 purposes; they are to describe the various Declarative Acts used by the students, to identify the style of Language Program students’ Declarative Acts, to identify the errors committed by students in their Declarative Acts in term of grammar and diction, and to identify the source of errors in their Declarative Acts. The subjects of this study are the eleventh grade students of Language Program at SMA Negeri 1 Tejakula. This study used elicitation technique and recorder, interview guide, and field note as the instruments in collecting the data. The data collection then were transcribed, analyzed and categorized, and then the result were described. The result of this study shows the Language Program students mostly produced five categories of Declarative Acts which the most dominant is to approve, then followed by to disapprove, to name, to call, and the last is to bless. The Language Program Students mostly produced Declarative Acts in informal language and followed by formal language. They also were not far from committing the errors. They frequently committed grammatical errors then followed by diction. From the students’ errors, there were five sources that caused errors in their Declarative Acts; they are interlingual errors, ignorance of rule restrictions, incomplete application of rules, false concept hypothesized, and developmental errors.keyword : Speech Acts, Declarative Acts, Language Program students